Effects of (-)-cubebin (Piper cubeba) on cytotoxicity, mutagenicity and expression of p38 MAP kinase and GSTa2 in a hepatoma cell line - Niwa, Andressa Megumi (2013)
(-)-Cubebin is a lignan extracted from the seeds of the pepper Piper cubeba, a commonly eaten spice with beneficial properties, including trypanocidal, anti-inflammatory, analgesic, anti-proliferative and leishmanicidal activities. Because of its therapeutic potential, we investigated the effects of (-)-cubebin on the cytotoxicity, cell proliferation kinetics, mutagenicity and expression of p38 MAP kinase and glutathione S-transferase a2 (GSTa2) using real-time RT-PCR in Rattus norvegicus hepatoma cells. We found that 280 μM (-)-cubebin was cytotoxic after 24, 48 and 72. h of exposure, but not mutagenic at 0.28 μM, 2.8 μM and 28 μM after 26. h. Similarly, exposure to 0.28 μM, 2.8 μM and 28 μM (-)-cubebin for 24, 48, 72 and 96. h did not alter the cell proliferation kinetics. Cells exposed to 28 μM (-)-cubebin for 24. h did not exhibit changes in p38 MAP kinase and GSTa2 expression, indicating that cellular changes were not induced by extracellular stimuli and that (-)-cubebin is likely not metabolized via this pathway. Our results suggest that high levels of (-)-cubebin should be consumed with caution due to the cytotoxic effect observed at the highest concentration. However, at lower concentrations, no cytotoxic, mutagenic or proliferative effects were observed, providing further evidence of the safety of consuming (-)-cubebin. © 2013 Elsevier Inc.